New style in teaching word processing - Arató, Mátyás; Bujdosó, Gyöngyi (Teaching Mathematics and Computer Science, 2006)
Teaching word processing is confined to looking through some menus and showing some functions of a word processor program, although technology presents just a small part of forming layouts. This fact causes that people who are writing documents spend a lot of time by trying to form, e.g., title pages or inner pages.The present paper deals with a design of an online course on word processing that fits better the needs of many users. The online course is designed for teaching (LA)TEX by leading the students to the technical issues of the typesetting system through layout and grammar rules: demonstrates the most important basic recommendations of typography and grammar rules through samples, and shows how to program the currently displayed layout in the (LA)TEX programming languages. This methodology suits better the common working habit, and can be a useful help in word processing documents.